2009
DOI: 10.1002/ps.1776
|View full text |Cite
|
Sign up to set email alerts
|

Persistence, metabolism and safety evaluation of thiamethoxam in tomato crop

Abstract: Thiamethoxam at normal and double the recommended use rate effectively controlled aphids, whiteflies and Helicoverpa, as the insect population decreased to a minimum within 10 days of spraying in comparison with the control. There was no significant difference between the two rates of application, and both thiamethoxam treatments significantly increased tomato fruit yield compared with the untreated control. A maximum residue limit (MRL) of 0.05 mg kg(-1) for tomato has been proposed, with a corresponding preh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(49 citation statements)
references
References 9 publications
3
44
1
1
Order By: Relevance
“…The half-life value of thiamethoxam obtained in this study was comparable with those previously reported on the dissipation of thiamethoxam from tomato (Abd El-Zaher et al, 2011), transplanted paddy (Barik et al, 2010 and green tobacco leaves . Moreover, Karmakar and Kulshrestha (2009) reported that thiamethoxam dissipated from 82% to 87% in 10 d with a half-life of 4 d in tomato fruits and total residues reached below detectable level in 15 d in tomato fruits.…”
Section: Discussionmentioning
confidence: 99%
“…The half-life value of thiamethoxam obtained in this study was comparable with those previously reported on the dissipation of thiamethoxam from tomato (Abd El-Zaher et al, 2011), transplanted paddy (Barik et al, 2010 and green tobacco leaves . Moreover, Karmakar and Kulshrestha (2009) reported that thiamethoxam dissipated from 82% to 87% in 10 d with a half-life of 4 d in tomato fruits and total residues reached below detectable level in 15 d in tomato fruits.…”
Section: Discussionmentioning
confidence: 99%
“…Bu insektisit, thianikotinil alt grubunda bulunan ikinci nesil bir nikonitik insektisittir. Thiamethoxamın tarım ürünlerini korumak için birçok emici ve ısırıcı zararlı böceklere karşı geliştirilmiş dünya çapında kullanılan en yararlı insektisitlerden birini oluşturduğu belirtilmektedir [5]. Bu insektisit ilk defa 1991 yılında tarım ilaçları pazarına dahil olmuştur.…”
Section: Thiamethoxamunclassified
“…The maximum residue limit (MRL) regulations require a preharvest interval (PHI) to ensure the dissipation of a pesticide below the proposed MRL at harvest time [15]. Field dissipation studies on pesticide persistence in primary agricultural products and pesticide residue behaviour in agricultural fields are necessary to ensure food safety and to protect the environment [16].…”
Section: Introductionmentioning
confidence: 99%